2024
DOI: 10.1186/s12889-024-18929-5
|View full text |Cite
|
Sign up to set email alerts
|

State of mental health, sleep status, and the interaction with health-related quality of life in HIV-infected Chinese patients during the COVID-19 pandemic

Juan Du,
Jin Li,
Han Liang
et al.

Abstract: Objective To describe how mental health and sleep status influence the health-related quality of life (HRQOL) of people living with HIV/AIDS (PLWHA) during the novel coronavirus disease 2019 (COVID-19) pandemic, and to apply targeted interventions to improve the HRQOL. Methods A web-based online questionnaire survey was administered. Descriptive analysis was used to depict the mental health and sleep status. Correlation analysis and the structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that sleep quality has a significant impact on health ( 15 , 16 ), especially among HCWs ( 17 , 18 ). Poorer sleep quality may lead to lower work productivity ( 19 ), more medical errors ( 20 ) and burnout ( 21 ) for HCWs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that sleep quality has a significant impact on health ( 15 , 16 ), especially among HCWs ( 17 , 18 ). Poorer sleep quality may lead to lower work productivity ( 19 ), more medical errors ( 20 ) and burnout ( 21 ) for HCWs.…”
Section: Introductionmentioning
confidence: 99%